AB0852 LONG TERM FOLLOW UP OF VISCOSUPPLEMENTATION WITH DIFFERENT TYPES OF INTRA-ARTICULAR HYALURONIC ACID IN OSTEOARTHRITIS OF THE KNEES. (2nd June 2020) - Aggarwal, A. K.; Aggarwal, N.; Jain, D.
Abstract : Background: Knee osteoarthritis (OA) is a progressive degenerative condition resulting in functional loss besides pain and discomfort.[1] The aim of treatment as of today should be joint preservation in order to prevent surgery, alleviation of symptoms and improvement of functions. Viscosupplementation (VES) with Intra-articular hyaluronic acid (IAHA) injections has been shown to have protective physiochemical functions and may confer disease-modifying, long term effects on the articular cartilage. [2][3] However conflicting guidelines, availability of multiple varieties, and absence of good studies or any treatment protocol has resulted in lack of confidence of the results of IAHA. Objectives: To determine the Long term effectiveness of VES with various types IAHA in OA in maintaining functional improvement of the knees and evaluate the duration of effect of first and repeat injections of VES. Methods: From the 15 year retrospective longitudinal study of data of VES with different types of IAHA in our Centre, we evaluated the following outcomes: The WOMAC scores were regularly done on each visit of the study group. Those with maintained improvement in the WOMAC total score were followed and reinjected when the scores started decreasing. All patients who were given Non Animal Source Hyaluronic acid (NASHA) were included in the study. Patients with repeat IAHA were further evaluated for Type of NASHA used and were categorized into 2 groups accordingly: a. Those with High Molecular weight Hyaluronic acid (HMW-HA) 6-8mg/ml – 6 ml single injections b. Those with Very High Molecular weight, Cross linked Hyaluronic acid (VHMW-HA) 20- mg/ml – 3 ml injections. Results: The total number of patients treated over the last 15 years was 1206 with 689 having Kellgren and Lawrence (KL) Grade III OA, and 517 KL Grade IV OA. The data showing distribution of type of IAHA used in the group, the average Gap between the injections with the Range in years for the least gap and the longest gap between the injections, along with the follow up to giving the 3rd injection was given is summarized in Chart 1: Time gap between repeat IAHL injections in OA knees. Conclusion: Repeated VES by IAHA were found to have a long term effect of alleviation of symptoms, improvement of functions and joint preservation and thereby prevention of surgery for a long period. VHMW-HA have a longer duration of action than HMW-HA. Repeat Injections bring about a similar duration of effect as the previous injection. References: [1]Mathers CD, Bernard C, Iburg KM, et al. Global programme on evidence for health policy. Discussion paper no. 54. 2003. http://www.who.int/healthinfo/paper54.pdf . Accessed 06 June 2019 [2]Henrotin Y, Raman R, Richette P, et al. Consensus statement on viscosupplementation with hyaluronic acid for the management of osteoarthritis. Semin Arthritis Rheum. 2015;45(2):140–149. [PubMed] [Google Scholar] [3]du Souich P. Absorption, distribution and mechanism of action of SYSADOAS. Pharmacol Ther. 2014;142(3):362–374. [PubMed] [Google Scholar] Disclosure of Interests: Anish Kumar Aggarwal Speakers bureau: Eli Lilly, Pfizer, Janssen of J&J, Dr. Reddy's, Intas, Torrent, Emcure & Alkem., NAKUL AGGARWAL: None declared, DIPIKA JAIN: None declared